2020
DOI: 10.1055/a-1113-7702
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss von MS-spezifischen Symptomen auf die gesundheitsbezogene Lebensqualität

Abstract: Zusammenfassung Hintergrund Multiple Sklerose (MS) ist eine chronisch progredient verlaufende Erkrankung, welche mit einer Vielzahl von MS-spezifischen Symptomen einhergeht. Viele dieser Symptome wirken sich negativ auf die gesundheitsbezogene Lebensqualität (Health Related Quality of Life, HRQoL) der Betroffenen aus. Bisher ungeklärt ist, welche MS-spezifischen Symptome einen besonders großen Einfluss auf die HRQoL haben. Methodik Die durchgeführte Untersuchung basiert auf den Daten einer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…In this study, from the results of the MSIS-29 questionnaire, which is a scale of physical and psychological impact perceived in MS, the patients demonstrated that MS affects the psychological domain more than the physical domain. This result is similar to the study conducted by Sander; Kugler; Elsner (2020) 46 who found that the main symptoms that interfere with the quality of life of MS patients are the so-called "hidden symptoms," such as depression, pain, and cognitive deficit, in addition to the change in mobility that also appears as an influencing symptom.…”
Section: Resultssupporting
confidence: 90%
“…In this study, from the results of the MSIS-29 questionnaire, which is a scale of physical and psychological impact perceived in MS, the patients demonstrated that MS affects the psychological domain more than the physical domain. This result is similar to the study conducted by Sander; Kugler; Elsner (2020) 46 who found that the main symptoms that interfere with the quality of life of MS patients are the so-called "hidden symptoms," such as depression, pain, and cognitive deficit, in addition to the change in mobility that also appears as an influencing symptom.…”
Section: Resultssupporting
confidence: 90%
“…The pain intensity after relapse was similar to that of a recent cross-sectional study on 431 patients with RRMS (independent of relapse), which reported 20% of patients being free of pain, 29% with mild pain, 31% with moderate pain, and 20% with severe pain [ 14 ]. Our patients had less pain 6 weeks after relapse onset than those in a recent German study that reported very mild background pain in 11.6%, mild pain in 16.2%, moderate pain in 37%, severe pain in 15.2%, and very severe pain in 4.1% of patients [ 1 ].…”
Section: Discussioncontrasting
confidence: 43%
“…For patients with MS, pain could be a more important non-physical impairment for determining QoL than social functioning, vitality, or general and mental health [ 21 ]. The presence of pain is a fundamental factor that influences QoL [ 1 ]. Physical impairment influences several domains of QoL, such as bodily pain, general health, vitality, and social functioning [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations